Analysis of Employee Services through a Community Approach in Increasing Customer Interests in Saving at BPRS Bhakti Sumekar - Jannah, Khozinatul; Romlah, Romlah; Sholihah, Imroatus (Yayasan Pendidikan Islam Bustanul Ulum Mojokerto, 2024)
BPRS Bhakti Sumekar KC Madya Pamekasan is a sharia financial institution which is surrounded by many large banks. The existence of these banks is a big challenge for BPRS Bhakti Sumekar KC Madya Pamekasan to survive and be able to compete. This research analyzes the relationship between employe service and customers’ interest in saving at BPRS Bhakti Sumekar KC Madya Pamekasan. Data was obtained through structured interviews with branch heads and marketing managers. To ensure the level of trust in the information, data triangulation was carried out using different techniques, namely observation of the environment and forms of community services implemented at BPRS Bhakti Sumekar. All data analyzed to describe the impact of employee services oninterest in saving at BPRS Bhakti Sumekar KC Madya Pamekasan. The research method involves in-depth interviews with employees and customers, as well as direct observatiton of service interactions. The findings show that employee service quality plays an important role in shaping customeers’ interes in saving, with interpersonal aspects and trust being the main factors. The implecations of this research can help BPRS Bhakti Sumekar in designing service strategies that are more effective and focus on customer needs and preferences The findings of this research show that customers' interest in saving is increasing due to adequate bonuses and community services that customers receive. Community services are provided in the form of football pick-up and drop-off services, balance printing services, and problem solving.